2019
DOI: 10.1093/aje/kwz037
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Sleep Characteristics With Cognitive Function and Decline Among Older Adults

Abstract: Sleep laboratory studies find that restricted sleep duration leads to worse short-term cognition, especially memory. Observational studies find associations between self-reported sleep duration or quality and cognitive function. However self-reported sleep characteristics might not be highly accurate, and misreporting could relate to cognition. In the Sleep Study of the National Social Life, Health, and Aging Project (NSHAP), a nationally representative cohort of older US adults (2010–2015), we examined whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
60
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 48 publications
3
60
2
Order By: Relevance
“…Previous studies 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 have investigated the longitudinal association between sleep duration and cognitive decline or dementia. Tworoger et al 12 analyzed data from the US Nurses’ Health Study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 have investigated the longitudinal association between sleep duration and cognitive decline or dementia. Tworoger et al 12 analyzed data from the US Nurses’ Health Study.…”
Section: Discussionmentioning
confidence: 99%
“… 6 Although a number of cohort studies 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 have examined whether baseline sleep duration was associated with cognitive decline and incident dementia, the results were inconsistent. Some cohort studies 7 , 8 , 9 , 10 , 11 observed sleep duration to be statistically significantly associated with cognitive decline and incident dementia, whereas other studies 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 did not reach this conclusion. However, the sample sizes of most previous studies 11 , 12 , 14 , 15 , 16 , 18 , 19 , 20 , 21 , 22 , 24 were small.…”
Section: Introductionmentioning
confidence: 99%
“…Second, in adjusted analyses, those who reported feeling rested “some nights” had better cognitive function over time. With an aging population in the United States, understanding the contributing factors to cognitive impairment and the initiation and worsening of AD is imperative ( 5 ). Results from our study offer clinical and practical utility in identifying the specific sleep difficulties that relate to cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…In research conducted among a nationally representative sample of men using both objective and self-reported measures, researchers found a proxy for sleep difficulty (i.e., self-reported poor sleep quality) and objectively recorded nighttime awakenings were associated with cognitive decline in the follow-up period, which was between 3 and 5 years ( 4 ). Another nationally representative study using both objective and self-reported measures did not find any significant associations between self-reported sleep difficulties and cognition during the 5 years, but researchers did find objective recordings of sleep fragmentation and waking after sleep onset were associated with cognitive decline ( 5 ). Results from cross-sectional analyses showed a significant association between insomnia (i.e., chronic sleep difficulty) and reduced performance in learning and temporal order judgment among older adults ( 6 ).…”
mentioning
confidence: 99%
“…Importantly, differences between measurements may impact upon observed relationships with cognitive outcomes. For example, the Sleep Study of the National Social Life, Health, and Aging Project (NSHAP), a nationally representative cohort of older US adults (2010-2015), found that actigraphic measures of sleep disruption were associated with worse cognition and higher odds of 5-year cognitive decline but there was no association for self-reported sleep [43]. As self-reported measures of sleep duration correlate well with daily sleep diaries [44], are the mainstay of population-based cohort studies, and are the focus of sleep guidelines, further studies using both objective and self-report measures of sleep duration to examine cognitive and MRI outcomes are needed.…”
Section: Discussionmentioning
confidence: 99%